THE RELATIONSHIP BETWEEN LEG EXPLOSIVE POWER AND ARM STRENGTH ON BREASTSTROKE SWIMMING PERFORMANCE OF YUDA 22 SWIMMING CLUB ATHLETES - Vindi Rizki Prayoga; Muhammad Suhdy (CV Grasta Glory, 2026)
This study aims to determine the relationship between leg muscle explosive power and arm muscle strength with breaststroke swimming performance among athletes of the YUDA 22 Swimming Club. The research used a quantitative approach with a correlational design to analyze the association between the variables. The population consisted of 20 athletes, and 10 athletes were selected as research subjects through simple random sampling. Data were collected using several standardized tests. Leg muscle explosive power was measured using the standing board jump test, while arm muscle strength was assessed through the push-up test. Breaststroke swimming performance was evaluated by recording the time achieved in a 50-meter breaststroke swim. The data obtained were analyzed statistically to determine the relationship between physical strength components and swimming performance. The results showed that leg muscle explosive power and arm muscle strength, either partially or simultaneously, did not have a statistically significant relationship with the breaststroke swimming performance of Yuda 22 Swimming Club athletes. Although these two variables contributed about one-third of the performance variation, this finding indicates that breaststroke swimming ability is more influenced by other factors such as technique, coordination, and psychological aspects.